Relaksasi Genggaman Jari untuk Menurunkan Tingkat Kecemasan Pasien Hipertensi - Itsnaani Rahmadita Nur Latiifah; Nurlaila Fitriani (FORIKES, 2022)
Uncontrolled hypertension can cause complex problems as complications. If the patient's coping response is not effective, it can cause anxiety. Some individuals are sometimes unable to control the anxiety they face, resulting in disharmony in the body. The purpose of this study was to determine the effect of finger grip relaxation techniques on reducing anxiety levels in hypertensive patients in the emergency room of UNS Hospital. The design of this research was pretest-posttest with control group. The study sample was 30 patients who were divided into 15 people for the control group and 15 people for the intervention group. The anxiety level of both groups was measured using the HARS questionnaire. Analysis of differences in anxiety levels between the pre and post treatment phases was carried out using a paired sample t-test. The results of the analysis showed p-value = 0.104 for the control group and 0.000 for the intervention group. It was concluded that the finger grip relaxation technique was effective in reducing anxiety levels in hypertensive patients.Keywords: hypertension; finger grip relaxation techniques; anxiety level ABSTRAK Hipertensi yang tidak terkontrol dapat menimbulkan masalah kompleks sebagai komplikasi. Bila respon koping pasien tidak efektif, maka dapat menimbulkan kecemasan. Beberapa individu terkadang tidak mampu mengontrol kecemasan yang dihadapi, sehingga terjadi disharmoni dalam tubuh. Tujuan penelitian ini adalah untuk mengetahui pengaruh teknik relaksasi genggaman jari terhadap penurunan tingkat kecemasan pada pasien hipertensi di ruang IGD RS UNS. Rancangan penelitian ini adalah pretest-posttest with control group. Sampel penelitian adalah 30 pasien yang dibagi menjadi 15 orang untuk kelompok kontrol dan 15 orang untuk kelompok intervensi. Tingkat kecemasan dari kedua kelompok diukur menggunakan kuesioner HARS. Analisis perbedaan tingkat kecemasan antara fase sebelum dan sesudah perlakuan dilakukan menggunakan paired sample t-test. Hasil analisis menunjukkan nilai p = 0,104 untuk kelompok kontrol dan 0,000 untuk kelompok intervensi. Dismpulkan bahwa teknik relaksasi genggaman jari efektif untuk menurunkan tingkat kecemasan pada poasien hipertensi.Kata kunci: hipertensi; teknik relaksasi genggaman jari; tingkat kecemasan